The infrapatellar fat pad fibrosis degree does not influence postoperative pain 6 months following patellofemoral arthroplasty - Franco, Domenico; Leite, Chilan B. G.; Schmidt, Sebastian; Stefano, Marco T. Di; Sherman, Nathan; Protzuk, Omar; Jacobs, Cale; Lattermann, Christian (The journal of knee surgery, 2025)
This retrospective study investigates whether the degree of infrapatellar fat pad (IFP) fibrosis influences postoperative pain 6 months following patellofemoral arthroplasty (PFA). Furthermore, this study explores whether sex and patellar height are impacted by the degree of IFP fibrosis. A total of 64 patients who underwent PFA from 2010 to 2023 were included, all of whom had a preoperative knee MRI and at least 1 year of follow-up. Patients were categorized into low (grades 0-1) and increased (grades 2-5) IFP fibrosis groups based on defined MRI findings. Pain outcome was assessed via a numeric rating scale. Demographic data, imaging parameters (e.g., preoperative Insall-Salvati index (IS), pre- and postoperative Caton-Deschamps index (CD), and patella morphology), and implant survivorship were analyzed. Contrary to the hypothesis, no significant association was found between IFP fibrosis degree and postoperative pain levels 6 months following PFA. Notably, the low IFP fibrosis group had a significantly higher prevalence of females (p = 0.02) and a higher preoperative IS index (p < 0.05), suggesting a connection among IFP fibrosis status, sex, and patellar height. No differences between groups were observed in age, body mass index, delta CD index, patella type, or implant survivorship. The lack of association between IFP fibrosis and postoperative pain suggests that IFP fibrosis may not be a determinant of PFA outcomes, potentially guiding surgeons to focus on other factors for optimizing postoperative pain management and implant success. Further studies are needed to elucidate the roles of sex and patellar height in the development of IFP fibrosis. The study provides level III evidence.